Policy analysis in France - Halpern, Charlotte; Hassenteufel, Patrick; Zittoun, Philippe (International library of policy analysis, 2018)
'Policy analysis in France' lays the foundation for a more systematic understanding of policy analysis in the country. In doing so, the volume discusses the role of the State and its restructuring, processes of government and governance, and State-Society relationships and policies as both a process and an outcome. Through 18 chapters contributions focus on policymakers, their practices, ideas and discourses, how they engage in sustained relationships with a large variety of market and society actors, and the concrete devices they use in order to make policy objectives operational. This is a comprehensive study of policy analysis in France that will be valuable to academics and postgraduate students researching and studying a range of policy and public management areas.